2014
DOI: 10.1002/brb3.246
|View full text |Cite
|
Sign up to set email alerts
|

Age of second language acquisition affects nonverbal conflict processing in children: an fMRI study

Abstract: BackgroundIn their daily communication, bilinguals switch between two languages, a process that involves the selection of a target language and minimization of interference from a nontarget language. Previous studies have uncovered the neural structure in bilinguals and the activation patterns associated with performing verbal conflict tasks. One question that remains, however is whether this extra verbal switching affects brain function during nonverbal conflict tasks.MethodsIn this study, we have used fMRI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 78 publications
(176 reference statements)
0
32
0
Order By: Relevance
“…In general, children tend to over‐recruit those same regions that are later engaged more efficiently by bilingual adults. For example, Mohades et al . tested bilingual and monolingual children using the Simon and Stroop tasks and found that bilingual children recruited the bilateral cingulate cortex to a greater extent than monolinguals on conflict trials.…”
Section: Bilingualism As a Model Of Efficiency: The Bilingual Anteriomentioning
confidence: 65%
“…In general, children tend to over‐recruit those same regions that are later engaged more efficiently by bilingual adults. For example, Mohades et al . tested bilingual and monolingual children using the Simon and Stroop tasks and found that bilingual children recruited the bilateral cingulate cortex to a greater extent than monolinguals on conflict trials.…”
Section: Bilingualism As a Model Of Efficiency: The Bilingual Anteriomentioning
confidence: 65%
“…One recent fMRI study adopting the Simon paradigm was reported by Mohades, Struys, Van Schuerbeek, Baeken, Van De Craen and Luypaert (2014), who compared activation in an event-related design across three groups of children: simultaneous bilinguals, successive early bilinguals, and monolinguals. Mohades et al found significantly higher activity in incongruent trials relative to congruent trials (in response to the increased demand in ignoring the position of stimulus) in both bilingual groups compared to monolinguals in the following brain areas: left superior temporal gyrus, bilateral posterior cingulate gyrus, right middle frontal gyrus, and right caudate nucleus.…”
Section: Common and Distinct Brain Regions Supporting Executive Contrmentioning
confidence: 99%
“…Some of the studies reviewed were not included into further analysis because there was not adequate information about either the maximum time allowed or how the data was treated (the 3rd study in Bialystok, Martin, et al, 2005, all studies in Gathercole et al, 2014, Yang et al, 2011, and Mohades et al, 2014. Carlson and Meltzoff (2008) was not included either because they did not report RTs.…”
Section: Meta-analysismentioning
confidence: 99%